Research note: utilizing a novel chicken ileal explant model to assess the efficacy of probiotic Limosilactobacillus reuteri CCM 9425 against Salmonella Enteritidis infection - Zuzana Kiššová; Gábor Mátis; Máté Mackei; Patrik Tráj; Rege Anna Márton; Dávid Géza Horváth; Csilla Tóthová; Dagmar Mudroňová; Viera Karaffová (Poultry Science)
The establishment of a consistent ex vivo model of poultry gut tissue for the study of intestine-microbiome interactions remains still a significant challenge. In this study a pro-inflammatory response of chicken ileal explant cultures was observed after Salmonella enterica serotype Enteritidis infection reflected by up-regulation of IL-18, TNF-α, IL-1β mRNA expression and the levelof serum amyloid A (SAA) protein. In contrast, pre-treatment of ileal explants with probiotic strain Limosilactobacillus reuteri CCM 9425 was able to suppress the infection-induced up-regulation of IL-1β, IL-18 cytokines and the SAA protein. Moreover, the applied probiotics elevated the RNA level of the gene encoding the anti-inflammatory cytokine IL-10 in the probiotic group and the pre-treatment group. Using ileal explant cultures isolated from chicken offers a reliable model of the gut, for studiing the effects of microorganisms at the level of histological tissue structure, gene expression of selected markers and protein production. In summary, regarding our results the miniature chicken ileal explants exhibited appropriate innate immune responses following exposure to bacterial infection with Salmonella Enteritidis and Limosilactobacillus reuteri, furthermore, represents a suitable model for the study of host-pathogen interactions under ex vivo conditions.